2010
DOI: 10.4314/ajtcam.v6i2.57085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying concentrations of the crude aqueous and ethanolic extracts of <i>Dalbergia sissoo</i> plant parts on <i>Biomphalaria pfeifferi</i> egg masses.

Abstract: This study evaluated, using replicated laboratory bioassays, the toxicities of the crude aqueous and ethanolic extracts of Dalbergia sissoo Roxb. 1832 (family Leguminosae) fruits, leaves, roots and stem bark against egg masses of Biomphalaria pfeifferi (Krauss, 1848), the snail intermediate host of Schistosoma mansoni (Sambon, 1907) in Nigeria. Viable 0-24 hr-old embryonated egg masses were separately exposed to five different concentrations (7.81-2000 mg/l) of extracts for 24 hrs, washed in dechlorinated tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Intensive studies have been conducted in search of agents which are more environmentally friendly to combat the intermediate hosts of Schistosoma . Efforts are directed particularly towards molluscicides of plant origin with several studies reported across the world [ 5 11 ]. Nevertheless, there is currently no licensed plant-derived molluscicide despite this myriad of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies have been conducted in search of agents which are more environmentally friendly to combat the intermediate hosts of Schistosoma . Efforts are directed particularly towards molluscicides of plant origin with several studies reported across the world [ 5 11 ]. Nevertheless, there is currently no licensed plant-derived molluscicide despite this myriad of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Mature green leaves were collected in October 2016 from a natural habitat located at 9°43′45.59′′ N, 39°73′2.71′′ E, central Ethiopia. It was dried in the shade and ground to fine powder of 200 μ m mesh size as in Adenusi and Odaibo [ 21 ]. It was stored in plastic bags in the laboratory of Environmental Health Science and Technology, Jimma University, Ethiopia.…”
Section: Methodsmentioning
confidence: 99%
“…Out of these 38 bands, 12 were monomorphic (shared among all groups) and 26 bands were polymorphic (Table 3). Data in table (4) revealed that cercariae exposed to S. nigrum (Group B) revealed a higher number (20) of polymorphic bands, and C. citrinus (Group C) revealed 16 bands which were different from those of control group either by presence or absence.…”
Section: Rapd-pcr Analysismentioning
confidence: 98%
“…Different weights of both plant extracts were dissolved in one ml dimethylsulfoxide (DMSO) then diluted by dechlorinated water [20] . The concentrations obtained for S. nigrum were 15 mg/L, 20 mg/L, 25 mg/L and 50 mg/L (21) , and for C. citrinus they were 20 mg/L, 30 mg/L, 40 mg/L and 60 mg/L [22] .…”
Section: Preparation Of Different Concentrations From Plants Extractsmentioning
confidence: 99%